Examining the Social Determinants of Seeking Help for Postpartum Mental Health - Agustin, Antonni Mikela (Archīum Ateneo, 2024)
Postpartum is a vulnerable period for women's health, and postpartum mental health issues, including postpartum depression, are growing concerns. Despite the increased awareness of mental health, several factors hinder women from seeking help for mental health concerns during the postpartum period. Hence, this qualitative study used the World Health Organization’s Social Determinants of Health Framework to examine the structural and intermediary determinants that shape women’s help-seeking behaviors regarding mental health during the postpartum period. A thematic analysis of interviews with 12 new mothers revealed that the structural determinants of help-seeking behaviors for postpartum mental health include employment status and working conditions as enablers and social perceptions of mental health, societal expectations of motherhood, and financial capabilities as barriers. This study also showed that intermediary determinants that enable help-seeking for postpartum mental health include effective communication, familiarity, informational support, perceptions of formal sources of help, and the severity of the situation. Conversely, hindrances include gaps in communication, inadequate emotional support, fear of being misunderstood, being gossiped about, and being a burden, belief in the responsibilities associated with motherhood, and belief in self-reliance. These findings can be used to develop initiatives to promote postpartum mental health.